Reframing Social Enterprise Policy in Indonesia Through Regulatory Analysis and Practitioner Insights - Palupiningrum, Agustina Widi; Winoto, Joyo; Achsani, Noer Azam; Sunito, Satyawan (School of Business, IPB University (SB-IPB), 2025)
Background: Social enterprises (SEs) in Indonesia had increasingly played a significant role in addressing multidimensional societal challenges through innovative, community-based approaches. Despite this progress, their development remained constrained by the absence of a coherent legal and institutional framework.Purpose: This study aims to critically examine the extent to which Presidential Regulation No. 2 of 2022 on National Entrepreneurship Development supports the growth and institutional legitimacy of SEs in Indonesia.Design/methodology/approach: Employing a comparative interpretive approach, the study combines critical legal document analysis with qualitative data from in-depth interviews involving twenty SE practitioners across various regions and sectors.Findings/Result: The analysis reveals a significant policy–practice gap. While SEs are referenced in the regulation, the absence of operational definitions, hybrid legal forms, incentive structures, and ecosystem support limits their recognition and functionality. In contrast, SE practitioners operate in informal and adaptive ways, innovating within fragmented institutional contexts and often without formal policy guidance.Conclusion: The findings underscore the need for institutional innovation and the co-creation of legal and policy mechanisms that are reflective of the hybrid realities of SEs. The study proposes the establishment of a dedicated legal framework, the development of tailored incentives, and the strengthening of a collaborative SE ecosystem in Indonesia.Originality/value (State of the art): This research contributes to the global discourse on social enterprise and open innovation by providing context-specific insights from a non-Western setting. It highlights the need for adaptive, inclusive regulatory approaches that bridge the gap between policy narratives and field-level realities in SE development. Keywords: hybrid organization, policy-practice gap, open innovation, regulatory framework, social enterprise